2016
DOI: 10.4143/crt.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time Interval between Breast-Conserving Surgery and Radiation Therapy on Outcomes of Node-Positive Breast Cancer Patients Treated with Adjuvant Doxorubicin/Cyclophosphamide Followed by Taxane

Abstract: PurposeThis study evaluated the effect of surgery-radiotherapy interval (SRI) on outcomes in patients treated with adjuvant radiotherapy (RT) after breast-conserving surgery (BCS) and adjuvant four cycles of doxorubicin/cyclophosphamide (AC) followed by four cycles of taxane.Materials and MethodsFrom 1999 to 2007, 397 eligible patients were diagnosed. The effect of SRI on outcomes was analyzed using a Cox proportional hazards model, and a maximal chi-square method was used to identify optimal cut-off value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“… 14 In a retrospective study of 397 patients, TTR after surgery of >7 months was associated with significantly compromised 6-year DFS (78% vs. 89%, p = 0.002) and DRFS (81% vs. 91%, p = 0.003) on univariate analysis, but such significances were missing on multivariable analysis. 15 Significant differences in DRFS and DFS were consistently observed in our study across the TTR after surgery groups on univariable analysis, but no significant impact was retained after adjusting for potential confounders on multivariate analysis. Intervals between surgery and RT depends on various patient-, tumor-, and treatment-related factors.…”
Section: Discussionmentioning
confidence: 49%
“… 14 In a retrospective study of 397 patients, TTR after surgery of >7 months was associated with significantly compromised 6-year DFS (78% vs. 89%, p = 0.002) and DRFS (81% vs. 91%, p = 0.003) on univariate analysis, but such significances were missing on multivariable analysis. 15 Significant differences in DRFS and DFS were consistently observed in our study across the TTR after surgery groups on univariable analysis, but no significant impact was retained after adjusting for potential confounders on multivariate analysis. Intervals between surgery and RT depends on various patient-, tumor-, and treatment-related factors.…”
Section: Discussionmentioning
confidence: 49%
“…is supports the evidence that receiving radiation or not could be considered as an independent variable. e time of radiation therapy after surgery is another challenging issue, which is not approved in many independent studies [40][41][42][43]. In a trial with 16 years follow-up, RT confirmed no increased risk of local recurrence when administered 2, 4, and 7 months after surgery and initial systemic therapy [44].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of paclitaxel to anthracycline-based regimens was associated with better local control for node-positive disease ( 16 ). One study showed no effect on clinical outcomes of delaying radiotherapy for more than 32 weeks after BCS and completing four adjuvant cycles of doxorubicin/cyclophosphamide and four cycles of taxane ( 17 ). A study from the MD Anderson Cancer Center also showed no significant difference in recurrence-free survival between patients with node-negative disease who started radiotherapy < 25 weeks and ≥ 25 weeks after BCS when chemotherapy was delivered ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address the imbalance of potential confounders of pretreatment variables, one-to-one patient matching without replacement was performed to pair cohorts of each group with a caliper size of 0.001 by propensity-score matching (PSM). We also used the Maxstat method to identify the optimal cut-off value of SCIT for outcomes ( 17 ). Statistical analyses were performed using SPSS Statistics v25.0 (IBM Corp., Armonk, NY, United States) and the “Maxstat” and “Matching” packages in R v3.4.4 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation